Elements of Organizational Culture - theoretical and methodological problems = Elementy kultury organizacyjnej - problemy teoretyczne i metodologiczne - Sułkowski, Łukasz (Zielona Góra: Faculty of Economics and Management Press)
The purpose of this article is therefore the analysis of the various elements of organizational culture that are present in different concepts of culture. This is an important problem from the point of view of theory and practice of managing organizations because it is through research and development that culture can be managed, or at least influenced. The article analyzes different elements of organizational culture that can be identified in empirical research. 13 different types of cultural components were identified, ranging from values to organizational subcultures.
Keywords: kultura organizacyjna; elementy kultury organizacyjnej; modele kultury organizacyjnej; organizational culture; organizational culture elements; models of organizational culture